2007
DOI: 10.1007/s00395-007-0674-z
|View full text |Cite
|
Sign up to set email alerts
|

Survival pathways in hypertrophy and heart failure: The gp130-STAT3 axis

Abstract: ■ Abstract Circulating levels of interleukin (IL)-6 and related cytokines are elevated in patients with congestive heart failure and after myocardial infarction. Serum IL-6 concentrations are related to decreasing functional status of these patients and provide important prognostic information. Moreover, in the failing human heart, multiple components of the IL-6-glycoprotein (gp)130 receptor system are impaired, implicating an important role of this system in cardiac pathophysiology.Experimental studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(99 citation statements)
references
References 170 publications
3
92
0
4
Order By: Relevance
“…IL-6 is a pleiotropic cytokine that induces multiple signals in different target cells (26) and has varying effects on myocardial function [recent review in (27)]. In mammalian cardiomyocytes, IL-6 signaling combines inflammatory activation with antiapoptotic survival pathway activation (28), preventing decompensation during cardiac overload (29).…”
Section: Relevance Of β-Adrenoceptor-mediatedmentioning
confidence: 99%
“…IL-6 is a pleiotropic cytokine that induces multiple signals in different target cells (26) and has varying effects on myocardial function [recent review in (27)]. In mammalian cardiomyocytes, IL-6 signaling combines inflammatory activation with antiapoptotic survival pathway activation (28), preventing decompensation during cardiac overload (29).…”
Section: Relevance Of β-Adrenoceptor-mediatedmentioning
confidence: 99%
“…Upon activation of JAK, STAT proteins dimerize and translocate to the nucleus, where they mediate gene transcription (reviewed by Sandberg et al [36]). In myocardial tissue it can be difficult to distinguish which receptor system is responsible for activation of JAK/STAT signalling [12]. Previous reports have shown that administrating insulin at reperfusion following ischemia/reperfusion induces cardioprotection via activation of a cascade of prosurvival protein kinases, including phosphatidylinositol 3-kinase (PI3K), Akt and p70s6 kinase [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The IL-6 family of cytokines mostly activates STAT3 and to a lesser extent STAT1 via a common receptor subunit (13). STAT proteins are also shown to be activated by interleukins indirectly through the activation of mitogen-activated protein kinases (MAPKs).…”
mentioning
confidence: 99%